Variabilidade climática regional da circulação oceânica no oceano Atlântico Equatorial Ocidental - MACHADO, Adilson Matheus Borges (2019)
The present study aimed to determine the annual cycle of the main surface oceanic fields and the interannual climatic variability of the Western Equatorial Atlantic Ocean (WEAO) in order to establish relations with strong and moderate El Niño and La Niña events in the Pacific Ocean. Given the importance of the climatic variability of the surface oceanic fields to the climate of the surrounding continents, the main motivation of this study is to explore the seasonal variability of Sea Surface Temperature (SST), Sea Surface Salinity (SSS) and of the surface currents in the WEAO simulations with a numerical model of regional ocean circulation. This study also analyzes the regional variability of the main surface oceanic fields on the interannual and decadal scale. The Regional Ocean Modeling System (ROMS) was used to simulate the SST, SSS, Sea Surface Height and Surface Velocity fields. The SST anomaly compounds in the WEAO for the different phases (El Niño x La Niña) and intensities (strong x moderate) of the El Niño Southern Oscillation (ENSO) phenomenon simulated by the ROMS model in the WEAO were calculated for the 4 regions of the Niño in the Equatorial Pacific Ocean. The results obtained from the numerical simulations were compared with reanalysis databases, observational satellite data and observational data collected in situ. The analyzes used include basic statistical metrics and the Empirical Orthogonal Functions (EOF) method, with the latter aiming to determine the main modes of variability of the SST and SSS fields. The pattern observed in the EOF of the filtered SST is consistent with the characteristics of the Atlantic Multidecadal Oscillation (AMO) and the Atlantic Meridional Mode (AMM). The present study pioneered in presenting the annual cycle of the main surface oceanic fields in the WEAO simulated on a regional scale for a period of 31 years, satisfactorily representing the main mesoscale oceanic processes in the region, also showing that the global climate phenomenon ENSO exerts a strong influence on the SST field of the WEAO. These results provide a new approach in the analysis of interannual climatic variability in the WEAO and its teleconnections with the Pacific Ocean, since this knowledge on a regional scale is a key element for the forecast of the weather and climate in the equatorial region.